2021
DOI: 10.1093/jrr/rraa141
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin alters the apelin-13/APJ pathway in certain organs of γ-irradiated mice

Abstract: Apelin-13 and APJ are implicated in different key physiological processes. This work aims at exploring the radioprotective effect of fucoxanthin (FX) on γ-radiation (RAD)-induced changes in the apelin-13/APJ pathway, which causes damage in the liver, kidney, lung and spleen of mice. Mice were administered FX (10 mg kg–1 day–1, i.p) and exposed to γ-radiation (2.5 Gy week–1) for four consecutive weeks. The treatment of irradiated mice by FX resulted in a significant amendment in protein expression of the apelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…These findings were supported by the physiological liver and kidney function measurements and histopathological investigation, whereas the changes in the architecture and functions of these tissues that responded to the oxidative damages and inflammation were observed. These data are in agreement with the previous findings shown in several studies by El Bakary et al, 10 Moustafa and Thabet, 26 Galal et al, 27 and Qin et al 6 These findings could be attributed to the overproduction of ROS, which induces an oxidative modification of biomolecules that is associated with the production of the proinflammatory mediators and initiates the inflammatory reactions through enhancing signalling cascades and activating transcription factors, subsequently causing an augmentation in the oxidative stress status and tissue damage. Whereas, during IR exposure, ROS has a negative effect on the cellular antioxidant defence mechanisms by decreasing the level of reduced glutathione and the activity of antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx), which is associated with an elevation in harmful oxidative molecules such as malondialdehyde (MDA), a prominent lipid peroxidation marker.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings were supported by the physiological liver and kidney function measurements and histopathological investigation, whereas the changes in the architecture and functions of these tissues that responded to the oxidative damages and inflammation were observed. These data are in agreement with the previous findings shown in several studies by El Bakary et al, 10 Moustafa and Thabet, 26 Galal et al, 27 and Qin et al 6 These findings could be attributed to the overproduction of ROS, which induces an oxidative modification of biomolecules that is associated with the production of the proinflammatory mediators and initiates the inflammatory reactions through enhancing signalling cascades and activating transcription factors, subsequently causing an augmentation in the oxidative stress status and tissue damage. Whereas, during IR exposure, ROS has a negative effect on the cellular antioxidant defence mechanisms by decreasing the level of reduced glutathione and the activity of antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx), which is associated with an elevation in harmful oxidative molecules such as malondialdehyde (MDA), a prominent lipid peroxidation marker.…”
Section: Discussionsupporting
confidence: 94%
“…These agents act via diverse mechanisms involving scavenging of free radicals and RO/NS, improving DNA repair process, synchronizing of cells, enhancing antioxidant and redox sensitive genes, modulating cytokines and growth factors, inhibiting apoptosis, and tissue regeneration. 10 Resveratrol (RSV) (3, 4, 5-trihydroxystilbene) is a polyphenol stilbene compound that is found naturally in red wine and in skin of red fruits and vegetables such as cabbages, berries, and peanuts. 11 It has anti-inflammatory, 12 anti-oxidant, 13 and anti-carcinogenic proprieties.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the histopathological examinations comprised in the present study might emphasis the biochemical changes discussed above and outlined the damages and changes induced by γ-radiation exposure in liver and spleen tissues architectures, which is confirmed with failure in liver functions enzymes (ALT and AST). 30 On the other side, administration of Ag before irradiation displays significant modulation of the biochemical and histopathological measurements encompassed in the current study (Figure 4 and 5). This could be explained in the light of Ag antioxidant and anti-inflammatory properties as reported previously in the finding of Kumar and Patnaik 44 and the study of Sajida and Prabhu.…”
Section: Discussionmentioning
confidence: 55%
“…14,37 The α-7nAchR is a primary receptor of the CAP (cholinergic anti-inflammatory pathway) that reveals anti-inflammatory reactions as well as the immune-modulatory response to keep immune homeostasis. 30 The study of Gao et al 38 found that the oxidative stress down-regulate α-7nAchR expression. Therefore, it could be explained the role of Ag in elevating the expression of α-7nAchR to its antioxidant abilities against ROS attacks and subsequent raised of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation